1999
DOI: 10.1209/epl/i1999-00156-5
|View full text |Cite
|
Sign up to set email alerts
|

Impurity scattering in isotropic p -wave superconductors

Abstract: The newly discovered superconductivity in Sr2RuO4 is most likely of p-wave. We study theoretically the impurity scattering in p-wave superconductors in the unitarity limit. A small amount of impurities not only reduces strongly the superconducting transition temperature, but also modifies dramatically the electronic properties. The present theory describes reasonably well a recent specific-heat measurement in Sr2RuO4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…This is consistent with the well-known universal thermal transport [29][30][31] of a superconducting state with line nodes; while it is completely different from what is expected for the isotropic chiral p-wave case. For isotropic chiral p-wave, the residual thermal conductivity becomes vanishingly small 33,34 in the zero impurity scattering limit, since the number of low energy excitations available for heat transport decreases rapidly below the isotropic superconducting gap and impurity induced sub-gap states are localized 35 .…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the well-known universal thermal transport [29][30][31] of a superconducting state with line nodes; while it is completely different from what is expected for the isotropic chiral p-wave case. For isotropic chiral p-wave, the residual thermal conductivity becomes vanishingly small 33,34 in the zero impurity scattering limit, since the number of low energy excitations available for heat transport decreases rapidly below the isotropic superconducting gap and impurity induced sub-gap states are localized 35 .…”
Section: Introductionmentioning
confidence: 99%
“…For Sr 2 RuO 4 the experiments of Nishizaki et al indicate that impurities strongly alter the low temperature properties even in the small impurity concentration limit [10]. This has previously been interpreted as an indication that Sr 2 RuO 4 is in the unitarity scattering limit [11]. Here it is shown that the Born approximation can explain the experimental results once the the unique microscopic (orbital dependent) nature of the superconducting state in Sr 2 RuO 4 is considered.The superconducting state described above is fully gapped so it is difficult to understand the experimental observation that only approximately half of the Fermi surface exhibited an energy gap [10].…”
mentioning
confidence: 56%
“…The object of this letter is to study the impurity effect in f-wave superconductivity. It is well known that impurity produces profound effect in unconventional superconductors [8,9]. Also for the analysis of transport properties the impurity scattering is crucial.…”
mentioning
confidence: 99%